Pyomelanin Synthesis in Alternaria alternata Inhibits DHN-Melanin Synthesis and Decreases Cell Wall Chitin Content and Thickness - Fernandes, Chantal; Mota, Marta; Barros, Lillian; Dias, Maria Inês; Ferreira, Isabel C. F. R.; Piedade, Ana P.; Casadevall, Arturo; Gonçalves, Teresa (Frontiers in Microbiology, 2021)
The genus Alternaria includes several of fungi that are darkly pigmented by DHN-melanin. These are pathogenic to plants but are also associated with human respiratory allergic diseases and with serious infections in immunocompromised individuals. The present work focuses on the alterations of the composition and structure of the hyphal cell wall of Alternaria alternata occuring under the catabolism of L-tyrosine and L-phenylalanine when cultured in minimal salt medium (MM). Under these growing conditions, we observed the released of a brown pigment into the culture medium. FTIR analysis demonstrates that the produced pigment is chemically identical to the pigment released when the fungus is grown in MM with homogentisate acid (HGA), the intermediate of pyomelanin, confirming that this pigment is pyomelanin. In contrast to other fungi that also synthesize pyomelanin under tyrosine metabolism, A. alternata inhibits DHN-melanin cell wall accumulation when pyomelanin is produced, and this is associated with reduced chitin cell wall content. When A. alternata is grown in MM containing L-phenylalanine, a L-tyrosine percursor, pyomelanin is synthesized but only at trace concentrations and A. alternata mycelia display an albino-like phenotype since DHN-melanin accumulation is inhibited. CmrA, the transcription regulator for the genes coding for the DHN-melanin pathway, is involved in the down-regulation of DHN-melanin synthesis when pyomelanin is being synthetized, since the CMRA gene and genes of the enzymes involved in DHN-melanin synthesis pathway showed a decreased expression. Other amino acids do not trigger pyomelanin synthesis and DHN-melanin accumulation in the cell wall is not affected. Transmission and scanning electron microscopy show that the cell wall structure and surface decorations are altered in L-tyrosine- and L-phenylalanine-grown fungi, depending on the pigment produced. In summary, growth in presence of L-tyrosine and L-phenylalanine leads to pigmentation and cell wall changes, which could be relevant to infection conditions where these amino acids are expected to be available.